Asymetria pomiędzy dobrem a złem z perspektywy filozoficznej i moralnoteologicznej - Tadeusz Kuźmicki (Studia Paradyskie)
In moral theology, the attainment of human activity assessment is based upon differentiation between what is good and what is evil. For this reason, the relationship between good and evil is so essential in moral theological reflection. Despite a preliminary impression that we might deal at this point with certain balance, the analysis of good from three perspectives, nonetheless, enables the obtainment of a different conclusion regarding evident asymmetry between good and evil. This asymmetry of good can be systematically analyzed three-dimensionally through the references to the thought of Thomas Aquinas, to the legacy of Neo-Thomist Josef Pieper, and to the reflections of an influential moralist Eberhard Schockenhoff. From a philosophical perspective, this asymmetry is observable in the analysis of a being, which, as created, is good in contradistinction to evil, which is nothing. From a moral-theological analysis of the genesis and purpose of human activity, good turns out to be the origin as well as the goal of human moral activity. Finally, from the third perspective, in exploration of aretology, good is considered, as early as by Aristotle, to be the highest rule in the dynamics of a virtue in general as well as in the realization of particular virtues.